2021
DOI: 10.3390/ijerph18020765
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Pelvic Floor Muscle Bioelectrical Activity (sEMG) Assessment Using a Multi-Activity Measurement Protocol in Young Women

Abstract: The aim of the study was to determine the between-trial and between-day reliability of the Glazer protocol and our multi-activity surface electromyography (sEMG) measurement protocol for pelvic floor muscle (PFM) evaluation. The bioelectrical activity of PFM was collected using an endovaginal electrode in 30 young, Caucasian, nulliparous women (age 22–27, 168.6 ± 5.1 cm, 57.1 ± 11.8 kg). The between-trial and between-day reliability of the original Glazer protocol and the new multi-activity sEMG protocol were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The evaluation of PFM functioning with the use of surface electromyography, measured during maximal voluntary contraction, showed good to excellent intra-rater reliability (ICC = 0.70–0.98), but the test–retest reliability was poor to good (ICC = 0.20–0.76). In another study, the PFM bioelectrical activity was reported as more reliable, and intra-rater, as well as test–retest, showing moderate to excellent reliability of both time-domains and quantitative parameters of PFM recruitment [ 32 ]. Nonetheless, as was underlined in those studies, the bioelectrical signal measured in the PFMs at rest and during different types of contraction may be influenced by many factors such as the type of vaginal probe, pelvis position during measurement, contact between the probe and surrounding PFMs, subject age or birth status [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The evaluation of PFM functioning with the use of surface electromyography, measured during maximal voluntary contraction, showed good to excellent intra-rater reliability (ICC = 0.70–0.98), but the test–retest reliability was poor to good (ICC = 0.20–0.76). In another study, the PFM bioelectrical activity was reported as more reliable, and intra-rater, as well as test–retest, showing moderate to excellent reliability of both time-domains and quantitative parameters of PFM recruitment [ 32 ]. Nonetheless, as was underlined in those studies, the bioelectrical signal measured in the PFMs at rest and during different types of contraction may be influenced by many factors such as the type of vaginal probe, pelvis position during measurement, contact between the probe and surrounding PFMs, subject age or birth status [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of a study by Auchincloss and McLean16 call into question the reliable use of surface EMG for between-subject comparisons or for use as between-day outcome measure. However, Oleksy and colleagues17 demonstrated good (intraclass correlation coefficient ≥ 0.80) between-trial and between-day reliability for average mean and peak amplitude PFM resting tone with 2 different protocols. Participants in both of these studies were adult women with assumedly better motor control ability to isolate PFMs during maximal contractions than children.…”
Section: Methodsmentioning
confidence: 97%
“…A maximum value of >35 μV was considered normal, while a maximum value of <35 μV indicated decreased slow muscle strength in the slow-twitch muscle phase (Type I fiber). 15 , 16 …”
Section: Methodsmentioning
confidence: 99%